A Comparison of Clients in a Differentiated Batterer Intervention Treatment Program: The Importance of Treatment Level Matching by Referral Sources - Claxton, Taylor L. (International journal of offender therapy and comparative criminology, 2021)
Recent research has emphasized the applicability of the Principles of Effective Intervention for batterer intervention treatment programs (BIPs), including using differentiated treatment models for first-time offenders compared to repeat offenders. The current study seeks to examine treatment matching across clients in two such differentiated BIPs from a mid-Atlantic state—one short-term program aimed at first-time IPV offenders (n = 121) and one program implementing BIP “as usual” (n = 125)—regarding client characteristics and recidivism. Findings indicate that clients in the short-term program were not significantly different than those referred to BIP “as usual” regarding common risk factors such as substance use, education, or employment, and while clients in the short-term program had fewer criminal history offenses, participants were rarely first-time criminal offenders. Further analyses showed no impact of the short-term program completion on client recidivism, while completion of BIP as usual was related to lower rates of reoffending among the program’s clients. Findings suggest the importance of how clients are matched to their level of treatment and more education and monitoring of referral agencies regarding differentiated BIP models. Further research is needed to assess whether short-term BIP programs are associated with recidivism reduction.